Metacognitive Strategies and Arabic Vocabulary Acquisition Through Listening Skills: Insights for AI-Assisted Language Learning - Suci Noor Asa Khaliza; Aulia Mustika Ilmiani; Maksudin (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
Vocabulary acquisition is a fundamental aspect of Arabic language learning, particularly in listening activities (maharah al-istimÄâ€™). This study explores the metacognitive strategies employed by students in acquiring Arabic vocabulary through listening skills and identifies the most dominant strategy used during the process. Using a descriptive qualitative approach, data were collected from students of the Arabic Language Education Program at the State Islamic University of Palangka Raya through observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and SaldaÃ±a. The findings revealed that students employed three metacognitive strategies: planning, monitoring, and evaluating. During planning, students prepared their focus and learning resources. During monitoring, they took notes on unfamiliar vocabulary, replayed audio, inferred meanings from context, and sought assistance when needed. During evaluating, they reviewed notes, consulted dictionaries, discussed with peers, and replayed audio to confirm understanding. Monitoring emerged as the most dominant strategy. The findings indicate that metacognitive strategies support more systematic and autonomous vocabulary acquisition and provide implications for the development of AI-assisted Arabic language learning environments.